2012
DOI: 10.1158/0008-5472.can-12-0979
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the HIF-1α/PDK3 Signaling Axis Drives Melanoma toward Mitochondrial Oxidative Metabolism and Potentiates the Therapeutic Activity of Pro-Oxidants

Abstract: Cancer cells can undergo a metabolic reprogramming from oxidative phosphorylation to glycolysis that allows them to adapt to nutrient-poor microenvironments, thereby imposing a selection for aggressive variants. However, the mechanisms underlying this reprogramming are not fully understood. Using complementary approaches in validated cell lines and freshly obtained human specimens, we report here that mitochondrial respiration and oxidative phosphorylation are slowed in metastatic melanomas, even under normoxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
111
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 48 publications
8
111
0
1
Order By: Relevance
“…Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref. 33) following treatment with vemurafenib, indicating that the drug may also be activating OxPhos in our model, in agreement with earlier findings (16,34).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we observed increased ROS production (to a similar extent as in previous publications; ref. 33) following treatment with vemurafenib, indicating that the drug may also be activating OxPhos in our model, in agreement with earlier findings (16,34).…”
Section: Discussionsupporting
confidence: 93%
“…Surprisingly, exposure to 0.55 mM DNP was not cytotoxic to melanoma cells and the DNP treatment caused an increase in ATP levels suggesting a metabolic adaptation to glycolysis (9). Several studies have shown that melanoma cells poorly respond to protonophore FCCP and are highly resistant to cytotoxic effects of OXPHOS inhibitors (47,48). These observations are consistent with the findings that the development of resistance to BRAF inhibition was associated with gain of mitochondrial functions (9 -12).…”
Section: Discussionsupporting
confidence: 80%
“…33 C-1311 is a better inhibitor for HIF-1a pathway inhibitor to exhibit better anti-tumor effects. 34 MicroRNA interference technique can effectively inhibit the progress of melanoma invasion.…”
Section: Discussionmentioning
confidence: 99%